2005
DOI: 10.1111/j.1365-2133.2005.06345.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma in patients with dermatitis herpetiformis and their first-degree relatives

Abstract: The present study documents that patients with DH can have both B- and T-cell lymphoma. The DH patients with lymphoma had not adhered as strictly to the gluten-free diet as the control patients without lymphoma. The occurrence of lymphoma in the first-degree relatives was lower than in the patients with DH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 24 publications
2
43
0
5
Order By: Relevance
“…In patients with DH the risk for intestinal lymphoma is significantly increased when the diet is neglected for a long period, particularly in the elderly (29) . One patient of the present study presented B-cell lymphoma at 54 years of age and was diagnosed as having CD and DH at the age of 33 years.…”
Section: Dermatological Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with DH the risk for intestinal lymphoma is significantly increased when the diet is neglected for a long period, particularly in the elderly (29) . One patient of the present study presented B-cell lymphoma at 54 years of age and was diagnosed as having CD and DH at the age of 33 years.…”
Section: Dermatological Disordersmentioning
confidence: 99%
“…The other patient, with DH and CD, diagnosed at 33 years of age, compliant to a GFD, IgA EmA negative, and without the use of dapsone, was diagnosed as having B-cell lymphoma (follicular type) at 54 years of age and is currently receiving chemotherapy. HERVONEN et al (29) reported 1% lymphoma in patients with DH that contracted the malignancy 2-31 years after the diagnosis of DH. A recent Swedish cohort study (73) raised the possibility of an increased risk for B-cell NHL in patients primarily affected with CD.…”
Section: Lymphomasmentioning
confidence: 99%
“…Of four patients who developed NHL, three were adhering to a gluten-free diet, but two for less than five years, which is probably a too short period to exhibit a protective effect against malignancy (Holmes et al, 1989). Extension of the follow up period for a further 12 years confirmed that patients who have adhered to a strict gluten-free diet for more than 5 years have no increased risk of developing lymphoma compared to the general population (Lewis et al, 1996), supporting the protective role of a gluten-free diet against lymphoma development in DH (Hervonen et al, 2005). Moreover, three patients had abnormal small bowel villous architecture, while one patient had normal mucosa, implying that a normal small bowel mucosa in DH does not protect from lymphoma.…”
Section: Dermatitis Herpetiformismentioning
confidence: 61%
“…Only one case was classified as EATL. DH indeed is not only associated with EATL, but also with Bcell lymphomas, which may occur both within and outside the gastrointestinal tract as nodal or extranodal disease (Hervonen et al, 2005, Viljamaa et al, 2006. One possible reason for this discrepancy may be the less severe small bowel damage in DH with respect to that in CD.…”
Section: Dermatitis Herpetiformismentioning
confidence: 99%
“…Tedavi edilmemiş hastalıkta görece risk yüksek olup glutensiz diet altında olanlarda risk düşmektedir 39 . Ayrıca B-hücreli lenfoma, deri lenfoması ve barsak adenokarsinomu da bu hasta grubunda gelişebilen maliniteler içinde yer alır 40,41 . Öte yandan, yakın zamanda yapılan bir çalışmada, dermatitis herpetiformisli hastalarda lenfoma gelişim riskinin toplum genelinden daha yüksek olmadığı saptanmıştır 42 .…”
Section: Dermatitis Herpetiformisunclassified